Analisi dello stato dell’arte delle fonti informative di uso e copertura del suolo prodotte in Italia - Pulighe, Giuseppe; Lupia, Flavio; Vanino, Silvia; Altobelli, Filiberto; Munafò, Michele; Cruciani, Sandro (GEOmedia, 2013)
Il progetto ITALI (Integration of Territorial And Land Information) nasce per rispondere alle esigenze dell'Ufficio Statistico dell'Unione Europea (Eurostat), con lo scopo di supportare, integrare e migliorare l'informazione statistica sulla copertura del suolo a livello nazionale correntemente prodotta dall'indagine europea LUCAS (Land Use/Cover Area frame Statistical survey). The aim of ITALI (Integration of Territorial And Land Information) project is the support, integration and improvement of information about land cover data currently produced by LUCAS survey, in order to produce official statistics consistent and regularly updated. The contribution reports the results of the first phase focussed on collection of all the available land use/cover datasets for Italy. After collection the datasets were compared by compiling a summary form, in accordance to the INSPIRE Directive, in order to highlight the specific features of each layer. Finally, an analysis of the classification systems was performed.